Uncommonly observed: the impact of New Jersey’s halfway house system - Hamilton, Zachary K. (Criminal justice and behavior, 2014)
Despite the nationwide use of halfway houses (HWHs), empirical findings documenting their impact have been generally infrequent over the last 30 years. Recent high-profile incidents have increased public attention and raised questions regarding their effectiveness and appropriate use. In response, this study provides information needed to fill the knowledge gap and answer policy questions through an analysis of 6,599 participants across 18 HWH programs in New Jersey. Participants were matched and compared with released inmates who were not provided a HWH placement. Using frailty models, an examination of five correctional outcomes revealed support for the effectiveness and continued use of HWH interventions, with regard to violating conditions of release resulting in revocations. Nonsignificant findings were identified for rearrests and convictions.